An Integrated Survey System for Addressing Abuse and Misconduct Toward Air Force Trainees During Basic Military Training - Keller, Kirsten M. (RAND Corporation, 2015)
The U.S. Air Force's Air Education and Training Command asked RAND to develop an integrated survey system to help address abuse and misconduct by military training instructors (MTIs) toward trainees during Basic Military Training. RAND developed two complementary surveys, one for trainees and one for MTIs. The report also includes recommendations about survey administration, reporting the results, and tracking and monitoring abuse and misconduct.